FAKTOR-FAKTOR DALAM PENGAMBILAN KEPUTUSAN PEMBANGUNAN INFRASTRUKTUR LINGKUNGAN MELALUI MUSYAWARAH RENCANA PEMBANGUNAN (MUSREMBANG) DI KECAMATAN PEKANBARU KOTA TAHUN 2014 - Juli Asnita; Febri Yuliani (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2017)
Infrastructure Development Environment is necessary for the community to support the life sustainability in the surrounding area. One of the tiered development program planning forum provided by the government to accommodate the aspirations of the community in terms of development is the Development Plan Council (Musrenbang). Musrenbang is a planning institutions in the region and as a mechanism to bridge the advance and necessity of the community (bottom up planning) with plan will be programmed by the government (top down planning). But through the process of development planning council in the district of Pekanbaru City, the results of the implementation of these activities is not in line with the expectations and advance of the society’s which is the genuine conditions and needs. The advance from the Pekanbaru Kota district can not be accommodated by the City government. The purpose of this study was to determine the decision making factors of Environmental infrastructure Development through Musrenbang in the Pekanbaru Kota district in 2014.The concept theory used to identify factors that exert influence is theory of decision making by Nigro and Nigro, which is: outside pressures, conservativeness, personality characteristics, influence from outside reference group, and other past conditioning. The research methodology used is descriptive analysis with qualitative approach. Method of data collection techniques in this study is observation, interview, and documentation by data analysis technique using Mies and Huberman model.The research result showed that the decision making process of environmental infrastructure development through Musrenbang in Pekanbaru Kota district in 2014 is ineffective due to overlook on community interest , not able to solve the existing problem in Pekanbaru Kota district, and not in the underlying interests of the communityKeywords : Decision Making, Musrenbang, Environmental Infrastructure